Portrait of David Oliphant Haynes (b. 1858) (1901)
Portrait of David Oliphant Haynes (b. 1858), father of chemical journalist and historian Williams Haynes (1886-1970). A native of Detroit, Haynes owned and operated D.O. Haynes & Co., a publishing firm that specialized in manufacturing industry and business-related publications like Pharmaceutical Era and New York Commercial.
Keywords: Journalism; Chemical industry; Haynes, Williams, 1886-1960; Haynes, David Oliphant, 1858-